Benthic foraminiferal faunas associated with cold‐water coral environments in the North Atlantic realm. (24th June 2021) - Fentimen, Robin; Schmiedl, Gerhard; Rüggeberg, Andres; Foubert, Anneleen
Abstract: Surface benthic foraminiferal assemblages associated with cold‐water coral mounds and reefs from the Irish margin and Norwegian shelf (North‐east Atlantic) are for the first time compared quantitatively. Results indicate that the considered sites share a common assemblage, dominated by elevated epibenthic and distinct infaunal species. This surface assemblage is typical of environments that are subject to strong bottom‐water turbulence with enhanced food availability. It provides a benchmark for comparison with fossil benthic foraminiferal assemblages from past cold‐water coral environments. Similar to macrofaunal and megafaunal communities, surface benthic foraminiferal diversity is higher on reefs and mounds than in surrounding off‐mound/off‐reef sediments. Benthic foraminiferal diversity is highest within the living coral macrohabitat, possibly as a result of enhanced availability and variety of food sources, and ecological niche separation. Indeed, living coral generally thrives on the summits or flanks of reefs and mounds where food availability is most important. The second part discusses the use of fossil benthic foraminiferal assemblages as palaeoceanographic proxies from past cold‐water coral environments. The overview of previous observations demonstrates that benthic foraminifera are valuable tools to reconstruct past bottom‐water oxygenation, bottom‐water currents and surface productivity, all of which are key environmental variables controlling cold‐water coral growth. Moreover, the advantages of a detailed investigation of benthic foraminiferal assemblages within cold‐water coral environments are compared to other palaeoceanographic proxies. This study highlights that benthic foraminiferal assemblages are an often overlooked proxy within cold‐water coral environments, despite yielding valuable information. Abstract : Surface benthic foraminiferal assemblages associated with cold‐water coral mounds and reefs from the North‐east Atlantic (Irish margin and Norwegian shelf) share a common assemblage, dominated by elevated epibenthic and distinct infaunal species. This surface assemblage is typical for environments that are subject to strong bottom‐water turbulence with enhanced food availability. In addition, the overview of past observations demonstrates that benthic foraminifera are valuable tools to reconstruct past bottom‐water oxygenation, bottom‐water currents and palaeoproductivity, all of which are key environmental variables controlling cold‐water coral growth.